A spatially explicit methodology for assessing and monitoring land degradation neutrality at a national scale - Gichenje, Helene Wanjiru (2019)
Land degradation is occurring in all parts of the terrestrial world, and is negatively impacting the well-being of billions of people. In recognition of the need for sustained global action on land degradation, the Sustainable Development Goals, adopted by the global community in 2015, include a specific goal aimed at halting the decline of land resources and achieving land degradation-neutrality (LDN) by 2030. The primary objective of this doctoral research was to operationalise the LDN target at the national level, using Kenya as the case study. The main research questions addressed in this dissertation have been positioned within a social-ecological systems framework in which ecosystems are integrated with human society. The first task of this research focused on determining the extent of land degradation and regeneration, and in establishing the LDN national baseline using the three LDN indicators (land cover, land productivity, and carbon stocks). This was then followed by identifying the key drivers that affect land degradation (browning) and land regeneration (greening) trends within the 4 main land cover types (agriculture, forest, grassland and shrubland), and within an area characterised by land cover change. The third task involved an assessment of the effectiveness of the current land-use policy framework, and associated institutions, to facilitate the implementation of LDN. Finally, in the last part of this dissertation, a climate-smart landscape approach at the water catchment level was proposed as a possible mechanism through which LDN can be operationalised at the sub-national level; Metodologia espacialmente explicita para a avaliação e monitorização da neutralidade da degradação do solo à escala nacional RESUMO: A degradação do solo é um fenómeno que está a acontecer em todas as partes do mundo terrestre, com impactos negativos no bem estar de milhares de milhões de pessoas. Reconhecendo a necessidade de uma ação global contra a degradação do solo, os Objetivos de Desenvolvimento Sustentável, adotados pela comunidade global em 2015, incluem um objetivo específico para travar o declínio de recursos terrestres e atingir a neutralidade de degradação do solo (NDS) até 2030. A presente tese de doutoramento teve como grande objetivo a operacionalização da NDS a nível nacional, usando o Quénia como caso de estudo. As principais perguntas de investigação consideradas nesta dissertação foram colocadas num enquadramento socio-ecológico, em que ecossistemas estão integrados com a sociedade. A primeira tarefa desta investigação consistiu em determinar valores de degradação e de regeneração do solo para estabelecer a base de referência de NDS nacional usando três indicadores de NDS (cobertura de solo, produtividade do solo e reservas de carbono). Seguidamente foram identificados os principais fatores que influenciam a degradação do solo (browning) e a regeneração do solo (greening) nas 4 principais coberturas de solo (agricultura, floresta, pastos e matos), bem como numa área marcada por alterações da cobertura de solo. Para a terceira tarefa foi avaliada a eficácia do atual quadro político sobre o uso de solo, bem como das instituições associadas, na viabilização da implementação da NDS. Na última parte da dissertação é adotada uma escala a nível da bacia hidrográfica, como uma abordagem “climate smart” adequada para a operacionalização da NDS a um nível sub-nacional.